Implikasi Putusan Mahkamah Konstitusi terhadap Demokrasi di Indonesia: Studi Yuridis-Normatif - Salam, Shelli Nur; Kurniasih (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The Constitutional Court of Indonesia plays a crucial role in maintaining constitutional supremacy and safeguarding democratic principles. However, its decisions have sparked debates regarding judicial neutrality, particularly in politically sensitive cases. This study aims to analyze the implications of the Constitutional Court’s rulings on democracy in Indonesia, focusing on their impact on the rule of law, political rights, and institutional checks and balances. A juridical-normative approach was employed, combining legal analysis of Constitutional Court rulings with empirical data on their implementation and effectiveness. The study examined 30 constitutional cases related to elections, civil rights, and governance from 2018 to 2023. Findings indicate that while 60% of the Court’s rulings reinforced democratic principles, only 35% were fully implemented by the executive and legislative branches, reflecting challenges in enforcement and institutional compliance. Furthermore, survey data from 1,000 respondents revealed that only 50% of the public understood the binding nature of Constitutional Court decisions, highlighting a gap in legal literacy. These findings suggest that while the Constitutional Court contributes to legal stability, its effectiveness is undermined by political interventions and weak enforcement mechanisms. Strengthening institutional accountability and public oversight is essential to ensuring the Court’s role as a guardian of constitutional democracy. This study contributes to the discourse on judicial independence by providing empirical insights into the challenges and opportunities for improving the effectiveness of constitutional adjudication in Indonesia.